1999
DOI: 10.1002/(sici)1097-4547(19991101)58:3<456::aid-jnr12>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Rasagiline, a monoamine oxidase‐B inhibitor, protects NGF‐differentiated PC12 cells against oxygen‐glucose deprivation

Abstract: In our in vitro model, rasagiline a selective irreversible monoamine oxidase-B (MAO-B) inhibitor, protected nerve growth factor (NGF)-differentiated PC12 cells from cell death under oxygen and glucose deprivation (OGD). The severity of the OGD insult, as expressed by cell death, was time-dependent. Exposure of the cells to OGD for 3 hr followed by 18 hr of reoxygenation caused about 30-40% cell death. Under these conditions, the neuroprotective effect of rasagiline was dose-dependent: rasagiline reducing OGD-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
0
23
0
Order By: Relevance
“…Typical in vitro ischemia experiments include exposure of cells to OGD for 0.5-15 h [8,[47][48][49]. Previously it was shown that 6 h OGD has minor effects on viability and can be used for ischemic preconditioning of PC12 cells, while development of ischemic tolerance occurs after 15-24 h of re-perfusion [8].…”
Section: In Vitro Ischemia Decreases H4k16acmentioning
confidence: 99%
“…Typical in vitro ischemia experiments include exposure of cells to OGD for 0.5-15 h [8,[47][48][49]. Previously it was shown that 6 h OGD has minor effects on viability and can be used for ischemic preconditioning of PC12 cells, while development of ischemic tolerance occurs after 15-24 h of re-perfusion [8].…”
Section: In Vitro Ischemia Decreases H4k16acmentioning
confidence: 99%
“…28,72,73 In addition, the neuroprotective activity of rasagiline is observable at concentrations below the MAO inhibition threshold and is observable in cell systems that do not contain MAO-B, such as human neuroblastoma SH-SY5Y. 74,75 In addition to SH-SY5Y, other isolated cell systems in which rasagiline has shown neuroprotective effects against a variety of challenges include NGFdifferentiated rat pheochromocytoma PC-12 cells, 5,76 fetal rat mesencephalic neurons, 77,78 rat hippocampal neurons, 31 rat cerebellar granule cells, 79 and fetal human mesencephalon cells 77 (Table IV). Under experimental conditions, rasagiline attenuates damage from toxins relevant to PD models such as 6hydroxydopamine, 80,81 N-methyl(R)salsolinol, 80,82 and N-morpholino sydonimine (SIN-1, a peroxynitrite donor).…”
Section: Neuroprotectionmentioning
confidence: 99%
“…There was also a significant and beneficial effect in quality of life (as assessed by the Parkinson's disease Quality of Life scale) compared to placebo. 13 In addition, non-clinical studies using multiple experimental models have shown that, independent of its MAO-B inhibitory activities, rasagiline is neuroprotective, as demonstrated by both in vitro [14][15][16] and in vivo animal models. [17][18][19] As monotherapy, rasagiline is considered safe and well tolerated, with frequency and types of adverse events for patients receiving rasagiline similar to those receiving placebo at daily doses of 1 and 2 mg, 8 and pain, headache and dizziness being the most common adverse events in both patients 20 and healthy volunteers.…”
Section: Introductionmentioning
confidence: 99%